Perbedaan Pemberian Jus Apel Hijau dan Air Rebusan Daun Seledri terhadap Tekanan Darah Wanita Menopause Hipertensi di Kabupaten Bojonegoro - Lia Rohmatin; Tri Yunita Fitria Damayanti; Idcha Kusma Ristanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Hypertension or high blood pressure is a chronic condition characterized by increased blood pressure on the walls of the arteries. Hypertension is caused by high sodium intake while vegetable and fruit intake is low. This study aims to determine the difference in blood pressure reduction in groups given green apple juice and boiled water from celery leaves in menopausal women who experience hypertension in Bojonegoro Regency. This type of research is quantitative research with a